Complexos fosfínicos de rutênio contendo o ligante 2,2’-dipiridilamina: síntese, caracterização e avaliação de suas atividades citotóxicas e de interação com DNA - Ribeiro, Gabriel Henrique (Universidade Federal de São Carlos, 2016)
This work aims the synthesis, characterization and evaluation of the biological activities of a series of mixed ligand ruthenium (II) phosphine complexes the containing 2,2’-dipyridylamine ligand. Furthermore, the studies of interaction of the complexes with calf thymus (CT) DNA were performed order to assess a possible mechanism of action of the complexes. The complexes synthesized were [RuCl(PPh3)(Hdpa)2]Cl (1), [RuCl(PPh3)(Hdpa)(bipy)]Cl (2), [RuCl(PPh3)(Hdpa)(dmbipy)]Cl (3), [RuCl(PPh3)(Hdpa)(fen)]Cl (4), [RuCl(PPh3)(Hdpa)(dphfen)]Cl (5) and [RuCl(PPh3)(Hdpa)(en)]Cl (6), where PPh3 = triphenyphosphine, Hdpa = 2,2’-dipyridylamine, bipy = 2,2’-bipyridine, dmbipy = 5,5’-dimethyl-2,2’-bipyridine, fen = 1,10-phenanthroline, dphfen = 4,7- diphenyl-1,10-phenantholine and en = diaminoethane. All complexes were characterized by molar conductivity, voltammetric techniques, elemental analysis, spectroscopic techniques (IR, UV-Vis, and 1D and 2D NMR) and the complexes (1), (3) and (6) have been structurally characterized by X-ray diffraction. The interaction studies of the complexes (1) – (4) and (6) with CT-DNA suggest reversible interactions through weak electrostatic attractions between the anionic phosphate backbone of the DNA and the monocationic complexes. However, the interaction studies by circular dichroism spectroscopy, agarose gel electrophoresis and viscosity measurements reveals that the complex [RuCl(PPh3)(Hdpa)(dphfen)]Cl causes significant changes in the DNA structure, which is consistent with a high-affinity DNA binding. The compound (5) might interact with the DNA via grooves binding and with contributions of hydrogen bonding of the amine group in the Hdpa ligand in the stabilization of the interaction. Further, the cytotoxicities of complexes against breast adenocarcinoma cell line (MDA-MB-231) and against chinese hamster lung fibroblast non-tumor cell line (V79-4) were evaluated. All the complexes demonstrated excellent cytotoxic activity against MDA-MB-231, with IC50 values in the range of 25.5 – 1.65 μmol L-1. Interestingly, complex (5) exhibits a cytotoxicity (IC50 = 1.65 ± 0.05 μmol L-1) higher than others complexes and with approximately 2 times more than cisplatin (IC50 = 2.44 ± 0.20 μmol L-1).
Phosphine ruthenium (II) complexes containing the 2,2’-dipyridylamine ligand: synthesis, characterization and evaluation of their cytotoxic activities and interaction with DNA
Keywords: Complexos Ru-fosfina; Interação com DNA; Atividade citotóxica frente MDA-MB-231; Ru-phosphine complexes; Interaction with DNA; Cytotoxic activites against MDA-MB-231 cells; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::CAMPOS DE COORDENACAO; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::QUIMICA BIO-INORGANICA